Neurobeachin, a promising target for use in the treatment of alcohol use disorder. (26th October 2021) - Cuzon Carlson, Verginia C.; Aylwin, Carlos F.; Carlson, Timothy L.; Ford, Matthew; Mesnaoui, Houda; Lomniczi, Alejandro; Ferguson, Betsy; Cervera‐Juanes, Rita P.
Abstract: Hazardous, heavy drinking increases risk for developing alcohol use disorder (AUD), which affects 7% of adult Americans. Thus, understanding the molecular mechanisms promoting risk for heavy drinking is essential to developing more effective AUD pharmacotherapies than those currently approved by the FDA. Using genome‐wide bisulfate sequencing, we identified DNA methylation (DNAm) signals within the nucleus accumbens core (NAcC) that differentiate nonheavy and heavy ethanol‐drinking rhesus macaques. One differentially DNAm region (D‐DMR) located within the gene neurobeachin ( NBEA ), which promotes synaptic membrane protein trafficking, was hypermethylated in heavy drinking macaques. A parallel study identified a similar NBEA D‐DMR in human NAcC that distinguished alcoholic and nonalcoholic individuals. To investigate the role of NBEA in heavy ethanol drinking, we engineered a viral vector carrying a short hairpin RNA (shRNA) to reduce the expression of NBEA . Using two murine models of ethanol consumption: 4 days of drinking‐in‐the‐dark and 4 weeks of chronic intermittent access, the knockdown of NBEA expression did not alter average ethanol consumption in either model. However, it did lead to a significant increase in the ethanol preference ratio. Following withdrawal, whole‐cell patch clamp electrophysiological experiments revealed that Nbea knockdown led to an increase in spontaneous excitatory postsynaptic current amplitude with no alteration in spontaneous inhibitory postsynaptic currents, suggesting a specific role of NBEA in trafficking of glutamatergic receptors. Together, our findings suggest that NBEA could be targeted to modulate the preference for alcohol use. Abstract : Understanding the molecular mechanisms promoting risk for heavy alcohol drinking is essential to developing more effective pharmacotherapies for alcohol use disorders. Genome‐wide bisulfate sequencing identified DNA methylation signals within the nucleus accumbens core that differentiated nonheavy and heavy ethanol‐drinking rhesus macaques. Further manipulation of the expression of a differentially methylated gene, neurobeachin ( NBEA ), in rodents resulted in alterations in ethanol preference. These findings suggest that NBEA could be targeted to modulate the preference for alcohol use.